2009
DOI: 10.1002/app.29854
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the phase structure, mechanical, rheological properties, and nonisothermal crystallization kinetics of the PEN/SCF composites

Abstract: Short carbon fiber reinforced poly(ethylene 2,6-naphthalate) composites (PEN/SCF) were prepared by twin-screw extruder. The structure, mechanical, rheological properties, and nonisothermal crystallization kinetics of the composites were investigated by scanning electron microscope, universal tester, and differential scanning calorimetry. The results suggest that there is better interaction between SCF and PEN matrix, which leads to an increase in the tensile strength, Young's modulus, and impact strength of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Only limited literature is available on the use of such polymer in composite applications. PEN has been used in continuous fiber form in composites based on epoxy resin, whereas it has recently been used as matrix for short fiber composites . PEN has been used for the first time as matrix for continuous fiber composites by Sorrentino et al , who prepared laminates based on glass fiber woven fabrics, and by Wang et al and Hine et al , who focused on the preparation of a single polymer composite (albeit they were only able to use a single reinforcing layer).…”
Section: Introductionmentioning
confidence: 99%
“…Only limited literature is available on the use of such polymer in composite applications. PEN has been used in continuous fiber form in composites based on epoxy resin, whereas it has recently been used as matrix for short fiber composites . PEN has been used for the first time as matrix for continuous fiber composites by Sorrentino et al , who prepared laminates based on glass fiber woven fabrics, and by Wang et al and Hine et al , who focused on the preparation of a single polymer composite (albeit they were only able to use a single reinforcing layer).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al reported on the isothermal crystallization kinetics, subsequent melting behavior, and the crystal morphology of PEN reinforced with short carbon fibers and they found that the addition of carbon fibers significantly improved the crystallization ability of PEN. In a subsequent article by the same authors , a significant increase in tensile strength, Young's modulus and impact strength due to the introduction of 10 wt% of short carbon fibers was reported. First attempts dealing with PEN composites reinforced with continuous reinforcement are those by Hine et al and Wang et al who reported on the fabrication of single polymer composites fabricated by the hot compaction method and the undercooling melt film stacking method, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Both physical and mechanical properties of a semicrystalline polymer are strongly dependent on crystallization behavior and morphology formed during polymer processing; therefore, studies on the crystallization and melting behavior are of great importance in understanding the interrelationship of processing-structure properties. The effect of fibers on crystallization of semicrystalline thermoplastics is a major concern in polymer science because of the technical importance of fiber-reinforced composites [31][32][33][34][35]. In this article, PA6/CF composites toughened with maleated elastomers were prepared by melt blending using twin-screw extruder via continuous fiber feed followed by injection molding.…”
Section: Introductionmentioning
confidence: 99%